2003
DOI: 10.1258/002221503322334558
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of primary mucosal head and neck squamous cell carcinoma using photodynamic therapy: results after 25 treated cases

Abstract: The use of photodynamic therapy for the treatment of malignant and non-malignant conditions is increasing. This paper demonstrates the efficacy of a second-generation photosensitizer, Foscan, in the primary treatment of a wide range of mucosal head and neck squamous cell carcinomas. Tumours ranged in stage from T(1) to T(3). A complete response to primary treatment was seen in 19/21 patients (90 per cent). In laryngeal cancer recurrent after radical radiotherapy, one out of four patients treated obtained a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Dilkes treated five patients with T1-2 laryngeal tumors with Foscan PDT. Only one of the five patients had no recurrence of disease [22].…”
Section: Early Stage Head and Neck Cancer: Foscan (Mthpc)-mediated Pdtmentioning
confidence: 87%
See 1 more Smart Citation
“…Dilkes treated five patients with T1-2 laryngeal tumors with Foscan PDT. Only one of the five patients had no recurrence of disease [22].…”
Section: Early Stage Head and Neck Cancer: Foscan (Mthpc)-mediated Pdtmentioning
confidence: 87%
“…Some patients received multiple PDT treatments. Of the 19 patients treated, 90% obtained a documented complete response and 10 of 19 patients remained free of disease with follow-up of 6-100 months [20][21][22]. Monnier treated four patients with Tis and T1 lesions of the oral cavity with a complete response [23].…”
Section: Early Stage Head and Neck Cancer: Foscan (Mthpc)-mediated Pdtmentioning
confidence: 99%
“…To date, this is the only photosensitizer that has been evaluated in multi-institutional trials for the treatment of head and neck cancers. Numerous single investigator trials have demonstrated the efficacy of Foscan PDT in treating head and neck cancers (20)(21)(22)(23)(24)(25).…”
Section: Early Stage Head and Neck Cancer: Foscan (Mthpc)-mediated Pdtmentioning
confidence: 99%
“…The current treatment standards include surgery, chemotherapy and radiotherapy. But all of these methods may cause serious side effects, often permanent, that hinder normal functioning of the body [26]. Extensive radiotherapy may cause mucositis, xerostomia, loss of taste and smell and even osteoradionecrosis.…”
Section: Cancer Therapymentioning
confidence: 99%
“…It is assigned for the palliative treatment of advanced head and neck cancers that did not respond to primary therapy [5]. It is usually injected at a dose of 0.15 mg/kg and activated with light at 652 nm after 4 days of delay [26]. The treatment protocol based on the use of this photosensitizer is directed to patients who cannot be subjected to surgery, chemotherapy or radiotherapy.…”
Section: Cancer Therapymentioning
confidence: 99%